2017
DOI: 10.1017/eaa.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

To Cut a Long Story Short: Formal Chronological Modelling for the Late Neolithic Site of Ness of Brodgar, Orkney

Abstract: Abstract:In the context of unanswered questions about the nature and development of the Late Neolithic in Orkney, a summary is given of research up to 2015 on the major site at the Ness of Brodgar, Mainland, concentrating on the impressive buildings. Finding sufficient samples for radiocarbon dating was a considerable challenge. There are indications from both features and finds of activity predating the main set of buildings exposed so far by excavation. Forty-six dates on 39 samples are presented and are int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Prior to any dated Neolithic activity, the landscape was dominated by grassland suitable for pasture. This natural prevalence of grassland may help to explain the rapid expansion of Neolithic settlement on Mainland, since the Neolithic Orcadian economy probably relied heavily on cattle (see Mainland et al, 2014;Card et al, 2017) and extensive clearance would not have been necessary to provide land for grazing. Inferred variations in the amount of "disturbed ground" above the baseline from the 4000 to 3800 cal BC timeslice onwards may hint at earlier anthropogenic disturbance by either late hunter-gatherers or farming pioneers; Sharples (1992) has suggested that the comparatively heavy FIGURE 3 | Example best-fit grids of land cover for Orkney case study in 200 year timeslices between 4200-2200 cal BC (age shown is midpoint of timeslice).…”
Section: Orkney: Neolithisation In a Largely Treeless Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to any dated Neolithic activity, the landscape was dominated by grassland suitable for pasture. This natural prevalence of grassland may help to explain the rapid expansion of Neolithic settlement on Mainland, since the Neolithic Orcadian economy probably relied heavily on cattle (see Mainland et al, 2014;Card et al, 2017) and extensive clearance would not have been necessary to provide land for grazing. Inferred variations in the amount of "disturbed ground" above the baseline from the 4000 to 3800 cal BC timeslice onwards may hint at earlier anthropogenic disturbance by either late hunter-gatherers or farming pioneers; Sharples (1992) has suggested that the comparatively heavy FIGURE 3 | Example best-fit grids of land cover for Orkney case study in 200 year timeslices between 4200-2200 cal BC (age shown is midpoint of timeslice).…”
Section: Orkney: Neolithisation In a Largely Treeless Landscapementioning
confidence: 99%
“…Whilst the crops and settlements of these Neolithic populations will have occupied a very small fraction of a landscape at any one point in time, the effects of these cultural practices will have been more widely seen, both through the impacts of grazing livestock and through the persistence of an ecological signal of disturbance for decades and sometimes centuries following abandonment and movement of the farming population. However, not all parts of the UK were fully wooded at the start of the Neolithic, and some of the most exciting archaeological finds of recent years (e.g., Ness of Brodgar; Card et al, 2017) come from the far North, where woodland cover was probably never complete in the Holocene, and certainly by the mid-Holocene the landscape contained extensive areas of naturally treeless grassland. Here woodland did not have to be cleared to permit agricultural activity, and indeed may have been sufficiently limited that it required deliberate protection.…”
Section: Introductionmentioning
confidence: 99%
“…To the west, a sizeable field system was uncovered, while in the south-west part of the Links (EASE Area 5) the excavators uncovered what they have described as 'a series of at least seven well-preserved dry stone buildings arranged in close proximity within a finely built stone-walled enclosure, linked by paved passageways and surrounded [and capped] by extensive and extremely rich midden deposits' (Moore & Wilson 2014); a Late Neolithic human skeleton was also found. One of the Area 5 structures (Structure 8, subsequently renamed Structure 10), a massive building some 22m across in its maximum extent (Moore & Wilson 2010a), closely resembles Structure 8 at Barnhouse (Richards 2005;Richards et al 2016) and Structure 10 at Ness of Brodgar (Towers et al 2015;Card et al 2017) in its size, shape and quality of construction. It was among the wallcollapse rubble within this building that the first (and most famous) of the Links of Noltland figurines was found (ie the so-called 'Westray wifie' or 'Westray Venus' (Moore & Wilson 2011a: illus 43)).…”
Section: A Brief History Of Discovery and Excavations On Links Of Nolmentioning
confidence: 99%
“…Here, on a pathway leading around the building, people had piled up thousands of bones -mostly cattle tibiae, split to extract the marrow, but also including a few non-cattle bones (Mainland et al 2014;Towers et al 2015;Card et al 2017). By the time of their deposition, that structure was already centuries old and possibly abandoned.…”
Section: Animals In Acts Of Structured Deposition In 3rd-millennium Cmentioning
confidence: 99%
See 1 more Smart Citation